KONTRIBUSI BIG FIVE PERSONALITY TERHADAP AGGRESSIVE DRIVING PADA REMAJA DI BUKITTINGI - Joni Herman; Yolivia Irna Aviani (Jurnal Riset Psikologi, 2018)
Abstract: Big five personality contribution to aggressive driving in teenagers in Bukittingi. This study aims to determine the contribution of big five personality to aggressive driving behavior in teenagers who ride motorbikes in Bukittinggi. The research design used in this study is a quantitative method. The population in this study were teenagers who ride motorbikes in Bukittinggi and the sample was withdrawn using purposive sampling technique by using certain criteria so that 90 subjects were obtained. Data collection techniques using aggressive driving scale from Houston, Harris and Norman which amounted to 37 items and big five personality scales from McCrew and Costa which amounted to 44 items and used multiple regression analysis techniques. Based on the research obtained the results of the regression value of p = 0,000 (p <0.05). Thus the hypothesis is accepted where there is a contribution between the big five personality to aggressive driving behavior in teenagers who ride motorbikes in Bukittinggi.Keywords: Big five personality, aggressive driving, teenagersAbstrak: Kontribusi big five personality terhadap aggressive driving pada remaja di Bukittingi. Penelitian ini bertujuan untuk mengetahui kontribusi big five personality terhadap perilaku aggressive driving pada remaja yang mengendarai sepeda motor di Bukittinggi. Desain penelitian yang digunakan dalam penelitian ini adalah metode kuantitatif. Populasi pada penelitian ini adalah remaja yang mengendarai sepeda motor di bukittinggi dan sampel ditarik dengan menggunakan tekhnik purposive sampling dengan menggunakan beberapa kriteria tertentu sehingga didapatkan subjek sebanyak 90 orang. Teknik pengambilan data dengan menggunakan skala aggressive driving dari Houston, Harris dan Norman yang berjumlah 37 item dan skala kepribadian big five dari McCrew dan Costa yang berjumlah 44 item dan menggunakan teknik analisis regresi berganda. Berdasarkan penelitian diperoleh hasil nilai regresi sebesar p= 0,000 (p<0,05). Dengan demikian hipotesis diterima dimana terdapat kontribusi antara big five personality terhadap perilaku aggressive driving pada remaja yang mengendarai sepeda motor di Bukittinggi.Kata kunci: Big five personality, aggressive driving, remaja